Formulation And Testing The Effectiveness Of Gel Extract Of Red Ginger (Zingiber officinale Var. Rubrum) As Antiinflamatory In White Male Rats (Rattus norvegicus). - Nurjannah Bachri; Nielma Auliah; Sri Wahyuningsih; Husna Dewi (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
Red Ginger is a type of rhizome that is widely used as an ingredient in traditional medicine in Indonesia. The efficacy of red ginger has been widely studied as an effective anti-inflammatory. One of the main components of red ginger is the gingerol class of compounds. This study aims to determine the anti-inflammatory effect that is applied to the red ginger extract gel (Zingiber officinale var. Ruburum) gel preparation with the HPMC gel-forming ingredient. The gel preparation was then tested for stability up to day 7 and evaluated for its anti-inflammatory power against white rats (Rattus norvegicus). The method used was the artificial inflammation ordering method, where the test was carried out by injection of carrageenan as a mediator for inflammation of the thighs of white rats, then topically giving Red Ginger extract gel with a concentration of 1%, 3% and 5%, HPMC as a negative control and diclofenac sodium as a Positive control. Measurements were carried out every 8 hours every day after being induced by carrageenan to use a caliper. The results showed that the reduction in inflammation to reduce the diameter of 1% after induction was 1.76 cm and decreased to 1.22 cm, the concentration of 3% after induction was 1.68 cm and decreased to 1.33 cm, the concentration of 5% after induction was 1 , 79 cm and decreased to 1.35 cm. Data were statistically analyzed using ANOVA showing that the negative HPMC controls did not show any anti-inflammatory effects. It can show that 1%, 3% and 5% Red Ginger ethanol extract gel has anti-inflammatory effects and the greatest effect is that the 5% concentration has an anti-inflammatory effect.